RSS and inertial navigation based indoor localization - Liu, Bowen (Nanyang Technological University, 2023)
With the rapid evolution of mobile Internet and mobile terminal equipment, the demand for location-based services is becoming increasingly robust. In addition, indoor activities have taken up most of people's time in the day, the importance of indoor positioning is constantly gaining attention. Since satellite signal is not available indoors, indoor positioning is also known as the last mile of positioning and navigation.